2012
DOI: 10.1371/journal.pone.0036471
|View full text |Cite
|
Sign up to set email alerts
|

Digital Gene Expression Profiling by 5′-End Sequencing of cDNAs during Reprogramming in the Moss Physcomitrella patens

Abstract: Stem cells self-renew and repeatedly produce differentiated cells during development and growth. The differentiated cells can be converted into stem cells in some metazoans and land plants with appropriate treatments. After leaves of the moss Physcomitrella patens are excised, leaf cells reenter the cell cycle and commence tip growth, which is characteristic of stem cells called chloronema apical cells. To understand the underlying molecular mechanisms, a digital gene expression profiling method using mRNA 5′-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 63 publications
3
34
0
Order By: Relevance
“…For research, moss tissue can easily be cultivated either on agar plates where gametophores are formed within few weeks or as protonema in liquid medium. Cells from a detached leaflet, a protoplast, or a wounded protonema filament undergo reprogramming to a meristematic protonema tip cell without the addition of exogenous hormones (Nishiyama et al 2012). Fig.…”
Section: Mosses Are Haploid Dominantmentioning
confidence: 99%
See 1 more Smart Citation
“…For research, moss tissue can easily be cultivated either on agar plates where gametophores are formed within few weeks or as protonema in liquid medium. Cells from a detached leaflet, a protoplast, or a wounded protonema filament undergo reprogramming to a meristematic protonema tip cell without the addition of exogenous hormones (Nishiyama et al 2012). Fig.…”
Section: Mosses Are Haploid Dominantmentioning
confidence: 99%
“…Scale bars: a 6 μm, b 50 μm, c 1 mm, d 500 μm, e 200 μm, f 100 μm This high regeneration capacity also supports the cultivation of moss tissue in liquid medium using weekly disruption cycles and the easy regeneration of plants from protoplasts. The molecular mechanisms underlying this pluripotency have been investigated and unraveled several key players including a basic helix loop helix transcription factor and two WUSCHEL-related homeobox 13-like genes (Busch et al 2013;Nishiyama et al 2012;Sakakibara et al 2014). …”
Section: Mosses Are Haploid Dominantmentioning
confidence: 99%
“…Deep sequencing of small non-coding RNAs (sRNAs) from the wild type, the DICER-LIKE 3 (DCL3)-deficient DPpDCL3 and DPpDCL4 mutants, enlightened the origin and biogenesis of specific sRNA classes (Cho et al, 2008;Arif et al, 2012) and deep sequencing of 5' ends of uncapped mRNAs (degradome) revealed microRNA (miRNA) biogenesis and target cleavage at a genome-wide resolution (Addo-Quaye et al, 2009). Recently, deep sequencing of 5' mRNA ends was used for a quantitative genome-wide expression analysis to study changes in gene expression during the reprogramming of leaf cells upon phylloid excision (Nishiyama et al, 2012).…”
Section: Moss Transgenesis 555mentioning
confidence: 99%
“…It is more advantageous than previous microarrays technology which has several limitations, including the accuracy of low abundance expression measurements, the differences of hybridization properties, and limitation to known genes (Wheelan et al, 2008). This technique has been widely used in transcriptomic studies in various species, including Caenorhabditis elegans (Nesbitt et al, 2010), Physcomitrella patens (Nishiyama et al, 2012), Cucumis sativus (Qi et al, 2012), Microsporum canis , Bombyx mori (Zhang et al, 2014), and Mus musculus (Zhang et al, 2013). Aiming to elucidate the molecular mechanisms of thermal stress tolerance in C. hongkongensis, a DGE based gene expression analysis was performed with Hong Kong oysters.…”
Section: Introductionmentioning
confidence: 99%